Implementation of Hypertension Management with Caregiver Empowerment to Improve the Quality of Life of the Elderly - Hariati, Hariati; Barus, Bunga Rimta; Sitorus, Friska Ernita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2025)
As they age, the elderly experience various declines in body system function which can increase the risk of developing various diseases. One of the health conditions most commonly suffered by the elderly is hypertension, which is one of the main causes of death in this age group. If not controlled properly, hypertension can cause serious complications which can be fatal for the sufferer. Therefore, the role of caregivers or family members is very important in helping elderly people manage hypertension effectively. The aim of this service is to improve the quality of life of elderly people suffering from hypertension. An intervention based on caregiver empowerment was carried out in the work area of ??the Deli Tua Community Health Center. This program method begins with an initial measurement of the quality of life of the elderly before intervention is carried out. Furthermore, caregivers are given education and training regarding the management of hypertension in the elderly which is monitored via the WhatsApp group. This monitoring lasted for one month, after which the quality of life of hypertensive elderly was measured again to assess the effectiveness of the intervention. The results show a significant increase in the quality of life of the elderly after caregiver empowerment. Before the intervention, the majority of elderly people, namely 54%, had a poor quality of life. However, after the program was running and interventions were implemented, this figure changed drastically, with 88% of elderly people showing an improvement in their quality of life. These results confirm that community service programs that focus on empowering caregivers in managing hypertension have a positive impact in improving the quality of life of elderly people suffering from this disease.